Sentimientos de madres con recién nacido hospitalizado - Marquina Calderon, Alexandra Johanna (2021)
The purpose of the following qualitative approach research with a descriptive method, dialectical approach aimed to describe and analyze the feelings of mothers with a hospitalized newborn. The theoretical approach was based on Ramona Mercer's “Maternal Role Attainment Theory", from which we took the concept: mother-child bond. The sample consisted of 7 mothers whose ages ranged from 20 to 40 years with children hospitalized in the Neonatology Service, in the Intermediate Care Unit III and IV of the Hospital Belén de Trujillo. The data was collected through semi-structured interviews. The content analysis of speeches was carried out of which 2 categories emerged: The first is Suffering vs. Maternal satisfaction and its dimension in Confronted maternal feelings. The second category is Practical Care vs. Humanized nursing care, having as a dimension of the Integrality of nursing care; On the other hand, the findings of our research show that mothers facing the process of hospitalization of the newborn were capable of generating various feelings and altered emotions; In addition, they impeded the development of her role as a mother, so she needs emotional support from the nursing professional, so that she can maintain the bond with her newborn